2021
DOI: 10.1186/s12986-021-00615-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming in cervical cancer and metabolomics perspectives

Abstract: Cumulative studies have shown that metabolic reprogramming is a hallmark of malignant tumors. The emergence of technological advances, such as omics studies, has strongly contributed to the knowledge of cancer metabolism. Cervical cancer is among the most common cancers in women worldwide. Because cervical cancer is a virus-associated cancer and can exist in a precancerous state for years, investigations targeting the metabolic phenotypes of cervical cancer will enhance our understanding of the interference of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…Cytokine and protein concentration were also different collected by endocervical swabs, lavage samples, and vaginal swabs (Dezzutti et al, 2011). Third, sequencing method, laboratory and data processing differ across studies, such as DNA extraction, sequencing target, platform, and annotation database may also impact the sequencing, metabolome and proteome result (Theodoridis et al, 2012;Schnaars et al, 2018;Mattei et al, 2019;Li and Sui, 2021;Sirichoat et al, 2021). For instance, the richness and diversity of cervical microbiota increased in HR-HPV positive women compared with healthy control by 16S rRNA sequencing, however, the difference were not obvious in metagenomic sequencing (Fang et al, 2022).…”
Section: Confounders Affect Microbiome Sequencingmentioning
confidence: 99%
“…Cytokine and protein concentration were also different collected by endocervical swabs, lavage samples, and vaginal swabs (Dezzutti et al, 2011). Third, sequencing method, laboratory and data processing differ across studies, such as DNA extraction, sequencing target, platform, and annotation database may also impact the sequencing, metabolome and proteome result (Theodoridis et al, 2012;Schnaars et al, 2018;Mattei et al, 2019;Li and Sui, 2021;Sirichoat et al, 2021). For instance, the richness and diversity of cervical microbiota increased in HR-HPV positive women compared with healthy control by 16S rRNA sequencing, however, the difference were not obvious in metagenomic sequencing (Fang et al, 2022).…”
Section: Confounders Affect Microbiome Sequencingmentioning
confidence: 99%
“…Dysregulation of the KP has been reported not only in males but also in females. 34 Therefore, it is necessary to elucidate the effects of diets on the KP in female mice. Moreover, we did not analyze critical metabolites, such as QUIN and KA, in the brain KP.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites, as indicators are valuable for identifying biomarkers of cervical cancer. Studies have reported that in the study of metabonomics about cervical cancer, samples were blood (serum or plasma), vaginal secretions, tissues, and urine [ 34 ]. A study reported that combination of lysophosphatidylcholine (17 : 0), n-oleoyl threonine, bilirubin, tetracosahexaenoic acid (lysoPC(17 : 0)), and 12-hydroxydodecanoic acidare are satisfactory candidate biomarkers for cervical cancer diagnosis from cervical cancer plasma samples [ 35 ].…”
Section: Discussionmentioning
confidence: 99%